Book selling and e-books in Sweden (Libellarium: journal for research in the field of information and related sciences, 2015)
This paper addresses the issue of the understanding of the book-selling situation as Swedish booksellers see it. It pursues the answers to the following questions:1. What are the perceptions of Swedish booksellers of the impact of e-books on their business?2. What drivers are important for Swedish booksellers for adopting and developing e-book sales through their own sales channels?3. What do they perceive as barriers to e-book selling through their own channels?The authors have employed the analysis of the secondary statistical data and a survey of Swedish booksellers to answer their questions.The results of the investigation have shown that the Swedish booksellers do not feel their bookshops, or business in general, are threatened by e-books. The opinions on e-books do not differ between the few selling e-books and others who do not offer this product. The reasons for selling e-books are well-functioning routines and personal interest in the product. The reasons for not selling the books are the lack of demand and technical resources as well as contractual agreements with e-book publishers or vendors. So, technical resources for e-book sales, routines, and contracts with publishers are the main premises for this activity.The biggest barriers to e-book sales are: a) the price as one can see not only in the answers of the booksellers, but also in the drop of sales obviously related to the rise of prices during 2014; b) lack of demand from customers who do not enquire about e-books in bookshops. This leads to the belief that e-books will be sold mostly online either directly from publishers and authors or through online booksellers. However, an equal number of booksellers believe that physical bookshops will be selling printed books and e-books in the future. The future of e-books seems to be quite secure and non-threatening to printed books from the point of view of booksellers. The growth of e-book sales is quite slow and the respondents believe that it will increase at a moderate rate.
Keywords: e-books; bookselling; bookshops; survey; Sweden